Autonomic dysfunction in a Jack Russell terrier - Caines, Deanne (Canadian Veterinary Medical Association, 2011)
A 4-year-old Jack Russell terrier was presented with an array of clinical signs suggestive of autonomic dysfunction. Many of the clinical signs were consistent with a diagnosis of dysautonomia; however, both chronicity and resolution of signs contradicted a diagnosis of this disease.